The Sea Fairies - Baum, L. Frank (Lyman Frank), 1856-1919 (Salt Lake City, UT : Project Gutenberg, 2003)
"The Sea Fairies" by L. Frank Baum is a children's fantasy novel published in 1911. Young Trot and her loyal companion Cap'n Bill are transformed into mermaids and journey into an underwater world of benevolent sea fairies. There they encounter Queen Aquarine's magical realm and face the villainous Zog the Magician, who enslaves sailors with his sea devils. Intended as the first in a new series, the book introduced characters who would later find their way into Baum's beloved Oz stories. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Sea_Fairies
Release date is 2003-08-01
Produced by Charles Aldarondo. HTML version by Al Haines.
Keywords: Fantasy literature; Sea stories; Voyages, Imaginary; Fairies -- Juvenile fiction; Mermaids -- Juvenile fiction; Sea monsters -- Juvenile fiction